Molecular characteristics of mismatch repair genes in sporadic colorectal tumors in Czech patients - Vymetalkova, Veronika Polakova (BioMed Central, 2014)
BACKGROUND: Mismatch repair (MMR) genes are known to be frequently altered in colorectal cancer (CRC). Both genetics and epigenetics modifications seems to be relevant in this phenomenon, however it is still not clear how these two aspects are interconnected. The present study aimed at characterizing of epigenetic and gene expression profiles of MMR genes in sporadic CRC patients from the Czech Republic, a country with one of the highest incidences of this cancer all over Europe. METHODS: Expression levels and CpG promoter methylation status of all MMR genes were evaluated in DNA from tumor and adjacent mucosal samples of 53 incident CRC patients. RESULTS: We have found significantly increased transcription levels in EXO1 gene in tumor tissues (P = 0.05) and significant over-expression of MSH3 gene in colon tumors when compared to adjacent mucosal tissues (P = 0.02). Interestingly, almost all MMR genes were differently expressed when localization of tumors was compared. In particular, colon tumors showed an up-regulation of EXO1, MSH2, MSH3, MSH6, and PMS2 genes in comparison to rectal tumors (P = 0.02). Expression levels of all MMR genes positively correlated between each other. The promoter methylation of MLH1 gene was observed in 9% of CRC tissues only. CONCLUSIONS: In our study, we have observed different pattern of MMR genes expression according to tumor localization. However, a lack of association between methylation in MMR genes and their corresponding expressions was noticed in this study, the relationship between these two aspects is worthy to be analyzed in larger population studies and in pre-malignant stages.